Collaborative Governance Dalam Pelaksanaan Program Pompanisasi dan Perluasan Areal Tanam Untuk Meningkatkan Produksi Tanaman Pangan di Kabupaten Tuban - Grace Febry Permata Putri; M. Kendry Widiyanto; Hasan Ismail (Public Sphere Review, 2025)
The involvement of various actors shows the importance of collaborative governance in dealing with complex and cross-sectoral environmental problems. Collaborative governance is needed as a response to the complexity of public problems that cannot be resolved effectively by a single actor. This approach aims to synergize the roles and contributions of various stakeholders through a participatory process, in order to optimize the program collectively. This multi-stakeholder involvement is directed at building synergy in encouraging collective motivation, increasing active participation, and strengthening the role of each actor in efforts to increase food crop production. Through a collaborative approach, it is hoped that an adaptive and inclusive governance mechanism will be created in facing the challenges of agricultural productivity amidst the threat of climate change. This study uses the Collaborative Governance theory developed by Stephan Balogh (2012) as an analytical framework to measure the effectiveness of collaboration in implementing the pumping and expansion of planting areas program in Tuban Regency. Balogh identified three main indicators in assessing the success of collaborative governance, namely: (1) collaboration dynamics, which include aspects of communication, trust, commitment, and resource availability; (2) collaborative actions, which include facilitation efforts and advancing the collaboration process; and (3) the impact and adaptation of collaboration, which focuses on the results of implementation and adaptive capacity to change. The research method uses a descriptive qualitative type with data sources taken by the author from the results of observations, interviews, and documentation supported by other secondary data. The collaboration process has not run optimally due to ego-sectoral, coordination gaps, and resource limitations. This shows that the prerequisites for effective collaboration have not been met.